Insight into the Effect of Adhesive Interface on the Ultimate Capacity of the Double-Superposed Shear Wall - Wenying Zhang; Lianping Yang; Shaole Yu; Xinxi Chen; Xuewei Zhang (Advances in Civil Engineering)
This paper presents the results of a numerical and analytical study to investigate the effect of adhesive interface on the ultimate capacity of a new composite sandwich shear wall: double-superposed shear wall. The effect of adhesive interface on the ultimate capacity of two different wall configurations under different axial compression ratios was studied. The results indicate that, for the two different wall configurations, the bond strength of adhesive interface has a negligible effect on ultimate bearing capacity. As a result of the different intensity grades between cast-in-situ concrete wythe and precast concrete wythe, the double-superposed shear wall with precast boundary elements (wall configuration W3) yields a higher ultimate bearing capacity than that with cast-in-place boundary elements (wall configuration W2), when the axial compression ratio exceeds 0.2, which is contrary to the results under 0.1 axial compression ratio. A new calculation method for ultimate bearing capacity is proposed to take into account the different intensity grades, and the calculation results show a very good agreement with the numerical simulation results.